DEVELOPMENT OF VIDEO VIRTUAL REALITY-BASED LEARNING MEDIA FOR PREECLAMPSIA AND ECLAMPSIA CASES IN CLINICAL CLERKSHIP - Sofyan Andri; Renardy Reza Razali; Yossi Mariati; Olivia Makmur (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: preeclampsia and eclampsia are high-risk pregnancy complications that can endanger both the mother and the fetus. The lack of clinical experience among young doctors in managing these conditions can impact their decision-making skills and patient management. Aims: the aims of this study to give innovative solution to enhance their competence in learning about preeclampsia and eclampsia with Virtual Reality (VR)-based learning media Methods: The method used in developing this media is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which uses a mixed quantitative and qualitative approach. VR media is developed by presenting interactive simulations that allow users to experience various clinical situations realistically and deeply. Results: Statistical analysis shows that the learning method using VR provides significant advantages in improving theoretical understanding, practical skills, and confidence of clinical clerkship compared to conventional learning methods. These results support the research hypothesis that the use of VR is more effective in the context of learning preeclampsia and eclampsia. Conclusion: the development of VR-based media has the potential to become an innovative tool supporting medical education, particularly in enhancing the preparedness of young doctors in managing critical obstetric cases Keywords: Virtual Reality, Learning Media, Pre-eclampsia, Eclampsia, Clinical clerkship